(Im)mobilising transnational labour? patterns of spatial mobility in Indo-German software companies. (1st October 2012) - Nicole Mayer-Ahuja
Abstract : Do transnational economic activities necessarily coincide with intensified spatial mobility, as debates about 'job nomads' or 'footloose capital' would suggest? Drawing on the results of a sociological research project on software programming in Indo-German project teams, it will be argued that this picture is far too simplistic. On the one hand, corporate strategies of labour utilisation vary markedly even within the software sector, partly implying a spatial mobilisation, but more often an immobilisation of labour. On the other hand, spatial mobility in its transnational, everyday and biographical dimensions is not determined by corporate strategies unilaterally, but closely interrelated with national standards of economic, social, and political regulation, in this case, in Germany and India respectively.